Study on the accumulation of zinc from soil to the biomass of lettuce (Lactuca sativa L. var. capitala L.) - Thanh Tran, Le Thi; Ha, Nguyen Van; Sinh, Nguyen Mong; Tuan, Nguyen Ngoc; Nhu Tien, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
The transport of heavy metals from soil to plants is a complex process depending on many factors. This study investigated the accumulated level of zinc – a heavy metal which plays an important role in the growth of plants and animals at a certain content and causes some diseases in these candidates at high concentrations – from soil contaminated by this element to lettuce. The results of this study showed that zinc can accumulate at high level in biomass of lettuce and zinc content in leaf was higher than its content in root. On the other hand, this investigation proved that the accumulating process of zinc from soil to lettuce was influenced by some factors including: soil pH, type and amount of mineral fertilizer used in cultivation and the presence of other heavy metals in soil. Keywords. Heavy metal pollution, accumulation of zinc, lettuce.